Palatability of Ground Beef Increases When Brand Is Disclosed in Consumer Testing - A. K. Wilfong; K. V. McKillip; J. M. Gonzalez; T. A. Houser; E. A. Boyle; J. A. Unruh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2016)
Of the beef products on the market, ground beef is one of the least expensive and most universal. Ground beef represents the largest volume of protein served in the foodservice industry, at 64%, and is the most popular beef item for consumers when preparing meals in their home (NCBA, 2012). To date, little research has evaluated ground beef palatability despite representing a large sector of the beef market. All ground beef is not the same to consumers. Ground beef from branded beef programs, higher lean points, and primal-specific blends are traditionally sold at retail for higher prices. Branding is used to indicate an increased quality level associated with the product, and encourages consumers to pay a premium in order to receive a superior product (Grunert et al., 2004). Certain branding strategies can influence consumers’ purchasing decisions even if they have not previously tasted the product (Levin and Gaeth, 1988). There is no conclusive evidence of how ground beef palatability changes with fat levels, although some studies have indicated products with higher fat levels are perceived to be more juicy (Myers et al., 2012). It is common for meat product studies to evaluate palatability differences in products through blind testing; however, consumers do not purchase and consume meat without being exposed to information about the product. Therefore, the objective of this study was to determine the effect of brand and product identification on consumer palatability ratings of ground beef patties.
Keywords: brand; palatability; ground beef